Characteristics of rainfall and erosion under natural conditions of land use in semiarid regions - Cleene A. de Lima; Helba A. de Q. Palácio; Eunice M. de Andrade; Julio C. N. dos Santos; Paulilo P. Brasil (Revista Brasileira de Engenharia Agrícola e Ambiental)
The characteristics of rainfall can provide important information for management and land use may also minimize the water erosion problems. This study was carried out to evaluate soil and water loss in erosion plots with different coverage, and the interference of natural rainfall characteristics on these processes. The experiment was carried out during the rainy season in the years of 2009 and 2010, on three erosion plots, each of 20 m², and under different land use conditions: native 'caatinga', thinned 'caatinga' and natural herbaceous cover. The rainfall was classified into three different rainfall patterns, characterized as early, intermediate and late. The predominant rainfall pattern for the two years under study was early rainfall with 47.6%, followed by intermediate and late with 30.5% and 22%, respectively. The smallest soil losses for the entire studied period were recorded for the native 'caatinga' plot, demonstrating the protective effect of vegetation on sediment production. Despite the early rainfall pattern being prevalent in the period of study, this was not the main factor responsible for water and soil loss.